The Influence of BPJS Health Services Quality on Patient Satisfaction at Ciseeng Public Medical Centre - Ade Anjalita Santi Dewi; Ernawati Ernawati (Journal of Social Science, 2023)
Badan Penyelenggara Jaminan Sosial (BPJS) is a legal institution established with the aim of managing health insurance plans and Indonesia is a country that has developed social security programs to help people in meeting their health needs. As the organizer of National Health Insurance (JKN), hospitals and Public Health Centre play a role to help a health service to the people of Indonesia. There are various indications to assess satisfaction to determine the quality or quantity of services consisting of Reliability, Assurance, Tangibility, Empathy and Responsiveness (RATER). The standard of service quality can be seen from the level of satisfaction that arises from a patient's feelings, if the level of patient satisfaction to a medical service is thus higher also the standard value of quality hospital or Public Health Centre services. Therefore, the researchers aim to assess the impact of BPJS health service quality on the level of patient satisfaction specifically at BLUD Public Health Centre Ciseeng, Bogor Regency, West Java Province, in 2021. The design of this study is cross-sectional. With analysis using The Exact Fisher test. The results of this study obtained the number of respondents who are satisfied with reability factors is as much as 83 (89.2%), assurance is as much as 83 (89.2%), tangible factors is as much as 85 (91.4%), empathy is as much as 84 (90.3%), and responsiveness is as much as 81 (87.1%). Statistical test results obtained a value of p = 0.000, which means there is a meaningful relationship between the quality of good service and satisfaction in the service obtained by patients. The advice for Public Health Centre is to continuously improve the quality of services in various dimensions to ensure satisfaction in BPJS recipient patients.